An Analysis of Online Game Influence Toward the Biology Learning Achievement of Students at SMAN 1 Suhaid and SMPN 1 Suhaid, Kapuas Hulu - Nawawi Nawawi; Yuver Kusnoto (Indonesian Journal of Biology Education, 2019)
This study aims to investigate the influence of online game toward biology learning achievement, dealing with the school environment and family environment of senior high school and junior high school students. The research method of this study is descriptive qualitative, which had been conducted at SMA N 1 Suhaid and SMP N 1 Suhaid, Kapuas Hulu, West Kalimantan. The sample is students who play online games. The technique of collecting data is using questionnaire in order to investigate online game users, interest factor in learning biology at school, and family factor. The technique of data analysis is using linear regression. Moreover, the result of the hypothesis test includes; (1) It is obtained that t > t table, or 2.789> 2.024. It means that there is an influence of online games toward biology learning achievement at SMA N 1 Suhaid in terms of the school environment. (2) The second hypothesis test results t < t table, or 0.903 <2.024. It means that there is no influence of online games in terms of family environment. (3) The result of the third hypothesis test results t > t table, or 2.132> 2.024. It means that there is an influence of online games toward the school environment. (4) The fourth hypothesis test results t > t, or 2.140> 2.024. It means that there is an influence of online game toward family environment.